Organic Fluorophores Conjugated with Pyridinium Acceptor: A Review on Design, Synthesis, and Application in Mitochondrial Imaging - Debnath, Pradip (Current Pharmaceutical Design, 2026)
Mitochondria are known as the powerhouse of eukaryotic cells. They play a crucial role in several biological processes and maintain cellular health. The ideal condition of mitochondria depends not only on their morphology but also on various micro-environmental factors, including pH, polarity, and temperature. Changes in these factors or malfunctions of mitochondrial species, such as Reactive Oxygen Species (ROS), active nitrogen species, metal cations, anions, and protons, can lead to several diseases in humans, including heart failure, kidney disorders, diabetes, Alzheimer’s disease, and Parkinson's disease. Therefore, monitoring Reactive Small Molecules (RSMs), maintaining micro-environmental factors, and estimating ROS levels in mitochondria are essential for understanding physiological behaviour and the pathogenesis of related diseases. Irregularities in mitochondrial function are closely linked to a range of clinical conditions, highlighting the importance of targeting mitochondria for therapeutic benefits. Over the last decade, numerous studies have focused on the development of small organic conjugated systems for mitochondrial imaging, utilizing optical signal transduction pathways. In this review, the design and synthetic strategies for small organic fluorophores conjugated with a pyridinium acceptor, their applications in mitochondrial imaging, and the detection of RSMs in mitochondria have been discussed. Studies have revealed that small-molecule fluorescent probes are being widely used for the detection and imaging of RSMs located in mitochondria. Moreover, this review covers the mechanistic insights, photophysical properties, biological characteristics of fluorophores, and therapeutic strategies targeting the mitochondria of human cells.
Keywords: Fluorophores